The Effect Of Sustainability Reporting On Company Value With Intellectual Capital As A Moderation - Dirman, Dirman; Muliyani Mahmud; Yustina Hiola (International Journal of Business and Quality Research, 2026)
This study examines the relationship between sustainability reporting and firm value and investigates whether intellectual capital strengthens this relationship in companies listed in the Jakarta Islamic Index (JII). Firm value is proxied by Price to Book Value (PBV), sustainability reporting is measured using the Global Reporting Initiative (GRI) disclosure index, and intellectual capital is assessed using the Value Added Intellectual Coefficient (VAIC™) model. The sample consists of 30 JII-listed firms in 2024, analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Drawing on signaling theory and the resource-based view, sustainability reporting is expected to function as a credible signal of long-term value creation, while intellectual capital is assumed to enhance the firm’s ability to transform sustainability disclosure into competitive advantage. However, the findings indicate that sustainability reporting does not significantly affect firm value, and intellectual capital does not moderate this relationship. These results suggest that sustainability disclosure in the Islamic capital market context may not yet be perceived as value-relevant information by investors. The absence of a significant effect also raises concerns regarding disclosure quality and the potential perception of greenwashing, where sustainability reporting fulfills regulatory compliance but lacks substantive strategic integration. The study contributes to the literature by highlighting the signaling limitations of sustainability reporting and the underutilized strategic role of intellectual capital in emerging Islamic markets.